Isavuconazole Therapy of Disseminated and Encephalic Saprochaete Capitata Infection in an Acute Myeloid Leukemia Patient Treated with Midostaurin - Perrone, Salvatore (Mediterr J Hematol Infect Dis, 2020)
BACKGROUND: Saprochaete capitata is a rare and emerging opportunistic fungus, involving immunocompromised hosts, in particular, neutropenic patients after chemotherapy. Case Report: We report a case of disseminated and cerebral infection by Saprochaete capitata, in a 68-year-old woman affected by acute myeloid leukemia that was successfully managed with liposomal amphotericin B and isavuconazole. CONCLUSIONS: This case illustrates the feasibility of isavuconazole therapy in the treatment of a S. capitata infection when co-administered with midostaurin.